CFD Analysis of Rear-Spoilers Effectiveness on Sedan Vehicle in Compliance with Malaysia National Speed Limit - Baharol Maji, Daniel Syafiq; Mustaffa, Norrizal (Journal of Automotive Powertrain and Transportation Technology, 2022)
A spoiler is an aerodynamic component used to decrease drag in automobiles. The primary function of the car rear spoiler is to increase the vehicle’s grip on the road by decreasing the aerodynamic drag and increase stability. This rear positioned device built up an area of high pressure to replace the low pressure on the trunk leading to increased stability. The objective of this study is to investigate the effects of rear spoiler on automobile aerodynamic drag and stability in compliance with the Malaysian National Speed Limit. Both the sedan vehicle model and the rear spoiler models were built using CAD (Computer-Aided Design) software. The data was then analyzed in CFD (Computational Fluid Dynamic) software to calculate the drag and lift force acting on the moving sedan car at velocity of 60km/h, 90km/h and 110 km/h. There have been some limitations due to the complexity of the design. Two rear spoiler designs which are the ducktail spoiler and the rear wing were used in the simulation along with the sedan vehicle. The result given by the simulations shows that rear spoilers increase the drag force and the downforce of the car. Rear wing shows a drastic increase in drag and downforce while ducktail spoiler shows a slight increase. The result also shows that slow moving vehicle has higher drag than fast moving vehicle. In summary, spoilers increase drag at low speed and only shows its benefits at high speed. Given the Malaysia National Speed Limit, spoilers may only show its benefit when the vehicle is driven on the expressway since expressways has a speed limit of 110 km/h.